Study on the performance of mesoporous sludge biochar for the removal of Rhodamine B - XIONG Yuting; LUO Caigui; TANG Xuekun; LUO Xianping (Gongye shui chuli)
In this study, modified sludge biochar(ASBC) was prepared by impregnation-pyrolysis method with municipal sludge as raw material and ZnCl2 as activator. ASBC/Peroxymonosulfate(PMS) system was constructed and used to degrade Rhodamine B(RhB). The effects of ASBC dosage, PMS concentration, reaction pH, and co-existing inorganic anions on the degradation of RhB in ASBC/PMS system were investigated. BET results showed that the specific surface area of activated biochar increased from 8.19 m2/g to 175.04 m2/g, pore volume increased from 0.017 cm3/g to 0.189 cm3/g, and activated sludge biochar had more active sites. When the dosage of ASBC was 0.2 g/L and the concentration of PMS was 0.8 mmol/L, the removal rate of RhB was as high as 99.7% after 5 min reaction, and the reaction could work in a wide pH range(3-11). H2PO4- and NO3- had no significant effect on the degradation of ASBC/PMS system, HCO3- had inhibitory effect and Cl- had promotional effect. RhB degradation by ASBC/PMS system was a non-radical pathway with 1O2 as the main active substance.